DEFENSIVE SYSTEM OF THE LEFT-BANK KYAT-KALA IN THE LATE MIDDLE AGES (XVII-XIX CENTURIES) (TAMADDUN NURI JURNALI, 2024)
The article is devoted to the results of the study of the defensive system of left-bank Kyat-Kala of the 17th-19th centuries. Based on these studies, the elements of the defensive system of the city are analyzed in particular. The defensive system built by Anushakhan at the end of the 17th century is explained by the great importance of the city in the history of the khanate as the center of a provincial principality.